Electrochemical Nitrogen Fixation for Green Ammonia: Recent Progress and Challenges - Haneul Jin; Suyeon S. Kim; Sandhya Venkateshalu; Jeseok Lee; Kwangyeol Lee; Kyoungsuk Jin (Advanced Science, 2023)
Abstract Ammonia, a key feedstock used in various industries, has been considered a sustainable fuel and energy storage option. However, NH3 production via the conventional Haber–Bosch process is costly, energy‐intensive, and significantly contributing to a massive carbon footprint. An electrochemical synthetic pathway for nitrogen fixation has recently gained considerable attention as NH3 can be produced through a green process without generating harmful pollutants. This review discusses the recent progress and challenges associated with the two relevant electrochemical pathways: direct and indirect nitrogen reduction reactions. The detailed mechanisms of these reactions and highlight the recent efforts to improve the catalytic performances are discussed. Finally, various promising research strategies and remaining tasks are presented to highlight future opportunities in the electrochemical nitrogen reduction reaction.